Pragmatic Analysis of Political Discourse: A Case Study of Presidential Debates - Evizariza Evizariza (Social Studies and Humanities Journal (SOSHUM), 2024)
Pragmatic analysis in the context of political discourse, especially in presidential debates, has become an important subject of study in understanding how language is used to influence public opinion and shape political images. This research aims to investigate the pragmatic strategies used by presidential candidates in debates to influence public opinion, with a focus on implicatures, speech acts, politeness strategies, and linguistic markers. The research method used is a systematic literature review by collecting and analyzing related articles from reputable international databases. The results of the discussion show that pragmatic analysis provides a deep understanding of the way political language is used by candidates to achieve their political goals and how it is interpreted by the public. The implications of this research include a better understanding of the dynamics of political communication, the influence of political language on public opinion, and its democratic implications. In conclusion, pragmatic analysis in the context of presidential debates makes a significant contribution to our understanding of political communication and democratic participation.